Speech Acts and Language Politeness on Community Based Tourism in The Bimo Coast, Banyuwangi - Aminulloh Aminulloh; Abdur Rosid (Universitas Muria Kudus, 2025)
This study examines the dimensions of politeness of speech acts in the interaction of coastal tourism management communities in Bimorejo Village, Banyuwangi. The main focus of this study is to reveal the forms of politeness of speech acts and the factors underlying community-based tourism (CBT). With an exploratory descriptive approach through observation, interviews, and documentation, it was found that the forms of speech acts used include locution, illocution, and perlocution, which are influenced by social, cultural, and pragmatic contexts. The results of this study provide important insights for community-based tourism management in Indonesia and encourage a broader understanding of the role of language in strengthening the tourism sector.